Through the Eyes of a Mapmaker: Maritime Shrines on Cyprus during the Late Middle Ages - Perdiki, Ourania (Religions, 2021)
Cyprus acquired special importance, especially from the thirteenth century onwards, on the Eastern Mediterranean’s pilgrimage network. Described by contemporary pilgrims as "Terra christianorum ultima", the island was considered to be the last Christian land in the south-eastern Mediterranean on the pilgrims’ itinerary on their journey to the Holy Land. This study is concentrated on two maps of Cyprus dated to the fourteenth century and preserved in Milan: Biblioteca Ambrosiana, A95 sup. and Venice: Biblioteca Nazionale Marciana, gr. XI.21. It aims to explore the physical and spiritual mobility and interconnectivity in Cyprus during the late Middle Ages and to consider how these contribute to the development of pilgrimage sites directly related with maritime routes, seamen and travellers. These unique nautical maps captured the sea voyage which had Cyprus as a stopover, bringing to light new insights into fourteenth century Cyprus. The maritime shrines discussed in this article, which are usually "mixed" sacred sites, are directly related with sailors’ needs. They integrate into a wide network of communication, removing them partially from their local dimension.